2019
DOI: 10.18203/2349-3291.ijcp20194718
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice in parents of chronically transfused thalassemic patients regarding thalassemia in thalassemia day care unit in government medical college, Amritsar, Punjab, India

Abstract: Background: Thalassemia is a chronic debilitating disease that affects nearly 200 million people worldwide. A caregiver who has good knowledge regarding the disease can not only provide a better quality of care to his/her ward but also may spread knowledge in the society in which he/she lives which helps immensely in raising community awareness related to the disease.Methods: 50 caregivers (either mother or father) of chronically transfused thalassemic children were questioned regarding their knowledge, attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…Additionally, mothers who live in urban areas have more opportunities to provide appropriate care due to the accessibility of healthcare facilities, programs, and workshops that increase awareness. This result is in line with Kalra et al (2019), who found a relationship between parents' practice about splenomegaly and their occupation and residence.…”
Section: Figure (2)supporting
confidence: 91%
“…Additionally, mothers who live in urban areas have more opportunities to provide appropriate care due to the accessibility of healthcare facilities, programs, and workshops that increase awareness. This result is in line with Kalra et al (2019), who found a relationship between parents' practice about splenomegaly and their occupation and residence.…”
Section: Figure (2)supporting
confidence: 91%
“… 50 Depression is a disorder of mental with changes in cognitive function, mood, behavior, and physical health, 51 which may be a result of the long-term treatment and chronicity of the thalassemia. 18 , 52 Depression and thalassemia have bidirectional relationships. Depressed patients with thalassemia had more fatigue, discomfort, pain, and sleep disturbance, while depression affects the physical and mental health of patients with thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…11,15 Patients with thalassemia face several problems during their lives, including the signs and symptoms of thalassemia, the presence of complications and comorbid chronic conditions, and treatment-related issues including painful injections and regular hospital visits due to blood transfusions. [16][17][18] It has been known that patients with thalassemia suffer from a wide range of psychological problems and health-related quality of life (QoL). 7,13,[19][20][21][22] They may develop anxiety and depression because of social problems such as uncertainties about the future and limited social activity.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian sebelumnya menunjukkan bahwa upaya pencegahan tidak memadai akibat dari kurangnya pengetahuan dan rendahnya kesadaran masyarakat luas tentang pencegahan. Data menunjukkan bahwa sebanyak 52,4% ayah dan 78,4% ibu yang memiliki anak dengan thalasemia memiliki pendidikan dasar yang kurang (tidak menempuh pendidikan formal); sebanyak 78,6% dari pasangan tidak menjalani skrining pranikah, dan sebanyak 71,2% pasangan tidak mengetahui tentang thalasemia minor sehingga anak mereka lahir dengan thalasemia mayor (Kalra et al, 2019). Penelitian lain juga mengungkapkan bahwa pengetahuan orang tua tentang thalasemia sangat rendah (Kharyal et al, 2021;Mat et al, 2020).…”
Section: Pendahuluanunclassified